SNPS em genes candidatos para potencial atlético como possíveis marcadores para desempenho em corrida em equinos da raça quarto de milha - Pereira, Guilherme Luis [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the Quarter Horse, different selection objectives led to the formation of lines with different skills, including racing and cutting. Less effective, but with great economic representation, the racing line present great sprinting speed over short distances on straight tracks. The cutting line is intended to evidence of functional character, exploring skills such as agility and obedience. The main objectives of this study were to estimate the allele and genotype frequencies of the g.38973231A>G (PDK4) and g.22684390C>T (COX4I2) SNPs in Quarter Horses (racing and cutting lines), as well as, in the racing line, to assess the occurrence of associations of these polymorphisms with performance trait (SI - speed Index); (2) verify the occurrence of differences in allele frequencies of g.66493737C>T (MSTN) and g.22999655C> (DMRT3) SNPs in racing line of contrasting to IV, and (3) to estimate genetic and environmental parameters for body measurements and IV of the racing line. The results showed the MSTN gene with the C allele near fixed with just an animal heterozygote (CT). In the analysis of 296 racing animals and 68 cutting animals, the differences in allele and genotype frequencies were statistically significant for PDK4 and COX4I2 genes between the two lines. The same was not observed when these frequencies were compared between extreme phenotypes race. There was also no significant effects on test of association between the alleles of the two polymorphisms and IV. The g.22999655C>A (DMRT3) SNP was genotyped in 60 animals. Heritability from 0.21 to 0.69 for morphometric traits and 0.17 for IV were observed. There was moderate negative correlation between body and rump length and performance (-0.44 and -0.30, respectively) and low positive correlation between height at withers and performance (0.25) that alleles. These results suggest of PDK4 and COX4I2 genes associated with better performance in race of PSI, perhaps are related ...

Dentro da raça Quarto de Milha, diferentes objetivos de seleção formaram linhagens com distintas habilidades, entre elas a de corrida e a de trabalho. Com menor efetivo, porém com grande representatividade econômica, a linhagem de corrida se destaca por possuir animais com capacidade de alcançar grandes velocidades em curtas distâncias. A linhagem de trabalho destina-se às provas de caráter funcional, explorando habilidades como agilidade e obediência. Os principais objetivos deste trabalho foram estimar as frequências alélicas e genotípicas dos SNPs g.38973231A>G do gene PDK4 e g.22684390C>T do gene COX4I2 em equinos Quarto de Milha de diferentes linhagens (corrida e trabalho) bem como avaliar a ocorrência de associações destes polimorfismos com características de desempenho (IV – Índice de Velocidade) na linhagem de corrida; (2) verificar a ocorrência de diferença nas frequências alélicas dos SNPs g.66493737C>T do gene MSTN e g.22999655C>A do gene DMRT3 em equinos Quarto de Milha da linhagem de corrida contrastantes para IV e; (3) estimar parâmetros genéticos e ambientais para medidas corporais e IV da linhagem de corrida da raça Quarto de Milha. Resultados do presente trabalho obtidos a partir de sequenciamento de DNA mostraram o MSTN com o alelo C próximo de fixado, com apenas um animal heterozigoto (CT). Na análise de 296 animais de corrida e 68 de trabalho, as diferenças de frequências alélicas e genotípicas se mostraram significativas para os genes PDK4 e COX4I2 entre as duas linhagens. O mesmo não foi observado quando estas frequências foram comparadas entre fenótipos extremos de corrida. Também não houve efeitos significativos no teste de associação entre os alelos dos dois polimorfismos e o IV. O SNP g.22999655C>A do gene DMRT3 foi genotipado em 60 animais. Foram observadas herdabilidades de 0,21 a 0,69 e 0,17 para medidas morfométricas e IV, respectivamente. Observou-se correlação ...
Keywords: Equino; Equino - Velocidade; Genetica animal; Cavalo de corrida; Cavalo de raça; Trabalho; Animal genetics